Impact of microsoft imagine cup on youth: a study on Microsoft Bangladesh Limited - Mahmud, Sakib (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.